2022
DOI: 10.1155/2022/4610522
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Melatonin Therapy in Patients with Myocardial Ischemia-Reperfusion Injury: A Systematic Review and Meta-Analysis

Abstract: Objectives. We conducted a meta-analysis to quantitatively evaluate the effect of melatonin therapy on patients with myocardial ischemia-reperfusion injury (MIRI) and explore the influencing factors. Background. Although preclinical studies have shown that melatonin can alleviate MIRI, its protective effect on MIRI in patients remains controversial. Methods. We searched PubMed, the Cochrane Library, and Embase. The primary outcome was cardiac function (left ventricular ejection fraction [LVEF], left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The doses of 10 mg/kg in mice imply equivalent doses of 0.81 mg/kg (around 50 mg/60 kg) in humans [ 38 ]. A recent review study for human myocardial ischemia-reperfusion injury found that intravenous route (with doses of 12–49 mg) of administration and early timing regimen benefit the cardioprotective effects of melatonin [ 39 ]. Melatonin is commonly administered orally in relatively small doses (1–10 mg) to humans but has a poor and variable bioavailability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The doses of 10 mg/kg in mice imply equivalent doses of 0.81 mg/kg (around 50 mg/60 kg) in humans [ 38 ]. A recent review study for human myocardial ischemia-reperfusion injury found that intravenous route (with doses of 12–49 mg) of administration and early timing regimen benefit the cardioprotective effects of melatonin [ 39 ]. Melatonin is commonly administered orally in relatively small doses (1–10 mg) to humans but has a poor and variable bioavailability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of melatonin in these organelles are an evolutionary feature resulting from eukaryotes engulfing melatonin-synthesizing bacteria, along with their subsequent transformation into mitochondria (Figures 2 and 4) [58]. Considering the seriousness of ischemic/reperfusion lesions, it is not surprising that melatonin has been extensively experimentally and clini-cally tested to overcome the damaging actions of oxygen/glucose deprivation at the level of cardiomyocytes [59][60][61].…”
Section: Melatonin's Protective Actions Against Cvd and Cardiac Damagementioning
confidence: 99%
“…Moving to cardiac effects, in a small scale, placebo-controlled double-blinded randomized clinical trial of 92 patients with HF and a reduced ejection fraction, nighttime MT at a dose of 10 mg decreased the concentration of natriuretic peptides and improved the quality of life of the patients, compared to placebo [ 147 ]. Moreover, in recently reported systematic reviews and meta-analyses, MT conferred cardiac protection and improved cardiac function [ 148 , 149 ]. At the same time, it reduced the level of cardiac injury markers, inflammatory cytokines, and oxidative markers while it increased the concentration of antioxidant factors [ 148 ].…”
Section: Antioxidant Pharmacotherapies In Cardiorenal Diseasesmentioning
confidence: 99%